DEFINING AND CONCEPTUALIZING GEOCULTURAL SCIENTIFIC LITERACY - BLYZNYUK , TETYANA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article offers detail analysis of the notion literacy from various perspectives; traces its evolution from the original understanding (the ability to read, write, and use arithmetic) up to the contemporary complex interpretation by numerous sources, encompassing the multiple meanings and scopes of unquestionably vital competencies. Besides, the author emphasizes the relevance of teaching/learning Geocultural scientific literacy as an education discipline in institutions of higher education in general and understanding its components in particular while preparing teachers for New Ukrainian School. The paper stresses that modern pedagogical education of Ukraine, is an integral component of the European educational space, aimed at forming a professional with firm scientific knowledge, ability to transmit it within the subjects of the academic process and is capable of active and effective livelihoods in a multinational and multicultural environment. Thus, solid knowledge of geocultural scientific literacy provides the perfect grounds for international cooperation in education sector, understanding uniqueness of relationships between the cultures, communities’ members, natural environments, politics, history and other measurements. This knowledge serves the basis for studying many university disciplines.